Two-dimensional (2D) covalent organic framework as efficient cathode for binder-free lithium-ion battery - Yao, Chang-Jiang (2020)
Searching new organic cathode materials to address the issues of poor cycle stability and low capacity in lithium ion batteries (LIBs) is very important and highly desirable. In this research, a 2D boroxine-linked chemically-active pyrene-4,5,9,10-tetraone (PTO) covalent organic framework (2D PPTODB COFs) was synthesized as an organic cathode material with remarkable electrochemical properties, including high electrochemical activity (four redox electrons), safe oxidation potential window (between 2.3 and 3.08 V vs. Li/Li+ ), superb structural/chemical stability, and strong adhesiveness. A binder-free cathode was obtained by mixing 70 wt % PPTODB and 30 wt % carbon nanotubes (CNTs) as a conductive additive. Promoted by the fast kinetics of electrons/ions, high electrochemical activity, and effective π-π interaction between PPTODB and CNTs, LIBs with the as-prepared cathode exhibited excellent electrochemical performance: a high specific capacity of 198 mAh g-1 , a superb rate ability (the capacity at 1000 mA g-1 can reach 76 % of the corresponding value at 100 mA g-1 ), and a stable coulombic efficiency (≈99.6 % at the 150th cycle). This work suggests that the concept of binder-free 2D electroactive materials could be a promising strategy to approach energy storage with high energy density.